Pengaruh Kualitas Pelayanan Terminal Kargo Terhadap Kepuasan Pengguna Jasa di Bandar Udara Sultan Babullah Ternate - Neli Awat Hi M Nur; Djoko Widagdo (Jurnal Multidisiplin Madani, 2022)
The growth in the number of passengers continues to increase every year, this is also followed by an increase in the number of postal and cargo transportation using airplanes, the purpose of this study is to find out how much influence the quality of cargo terminal services has on service user satisfaction at the airport of Sultan Babullah Ternate, service quality is the success of an achievement of a company in creating positive thinking from customers can also make customers feel satisfied. The method in this research uses quantitative methods or data collection is obtained from primary data with the questionnaire method. The population in this study are users of cargo terminal services in Sultan Babullah Airport Ternate, in this study requires a sample of 100 respondents. the sample or data source is selected using Non-Probability Sampling with Incidental Sampling Technique. The results in this study have an effect on the quality of cargo terminal services on service user satisfaction at Sultan Babullah Airport, Ternate. Showing the output results obtained from the beta coefficient value is 0.983 with t count that is 53.628 and t table is 1.98447 because t count > t table then Ho is rejected and Ha is accepted. In conclusion, the variable (X) of service quality has an influence on the variable (Y) of service user satisfaction with an effect of 0.983 or 98.3%.